An energy consumption improvement method for centrifugal pump based on bionic optimization of blade trailing edge. (1st May 2022) - Lin, Yanpi; Li, Xiaojun; Zhu, Zuchao; Wang, Xunming; Lin, Tong; Cao, Haibin
Abstract: The centrifugal pump is one of the most widely used types of power machinery in the water resource utilization and chemical industries. Its energy consumption cost accounts for a large proportion of its total economic cost. In this paper, an energy consumption improvement method for centrifugal pump is proposed by referring to the bionic structure to reduce the energy loss of the centrifugal pump. Four types of impellers with different types of sinusoidal tubercle trailing edges (STTE) are designed. Experiment and numerical simulation are combined to explore the beneficial effects of STTEs. Experimental research shows that this structural change will not affect the performance of the pump. On this basis, the entropy generation rate analysis method was introduced, and the numerical calculation results were analyzed to explore the internal influence of the STTE on the energy loss characteristics of the centrifugal pump. Results show that the use of STTEs can adjust the proportion of energy loss of each component in a centrifugal pump and effectively reduce the overall energy loss. Quantitative research indicated that the STTE3 has the optimal effect of reducing energy consumption. The use of STTE3 can reduce the total energy consumption by more than 5% at all flow rate conditions and reach a peak of 16.95% under 1.2 times nominal flow rate conditions. Thus, the bionic structure optimization method to improve the internal energy loss characteristics of centrifugal pumps will be beneficial and can provide a certain degree of reference for the hydraulic design of centrifugal pumps. Graphical abstract: Image 1 Highlights: An energy consumption improvement method based on bionic design is proposed. Impellers with different sinusoidal tubercle trailing edges are designed. Entropy production theory is introduced as the evaluation index. The STTE is expected to reduce energy consumption by more than 10%.